Komodifikasi Ruang Privat dalam Tayangan Pernikahan Atta Halilintar & Aurel Hermansyah - Fakhrizal Octaviana; Yadi Supriadi (UNISBA Press, 2023)
Abstract. At the beginning of 2021, the Indonesian television world was enlivened by a series of broadcasts of the weddings of top Indonesian artists. Atta Halilintar and Aurel Hermansyah. The popularity of both is an important source when the media displays a broadcast because it will be the center of attention of the audience. One of the highlights is the broadcast